Prazer e sofrimento nas vivências do trabalhador de enfermagem em pronto socorro pediátrico - Lamb, Fabricio Alberto (2015)
The aim of this study was to identify the experiences of pleasure and suffering in nursing workers‟ interaction with children and their families and also the defensive strategies used by these workers. The theoretical framework employed in the present study is the Psychodynamics of Work, which refers to the dynamic analysis of psychological processes involved in the confrontation of the individual with the reality of work. It is an exploratory and descriptive research with a qualitative approach, which took place at a University Hospital in southern Brazil. The techniques employed for data collection were the application of a questionnaire with socio-demographic and work-related information, and a focus group. The data analysis was conducted through Thematic Content Analysis. The results are presented in two articles. The first one, „‟The emergency of pleasure and suffering in nursing work at Pediatric Emergency Care Units‟‟, presents and analyses the daily experiences generating pleasure and suffering at Pediatric Emergency Care Units. The second one, „‟Nursing work defence strategies at Pediatric Emergency Care Units‟‟, identifies and analyses the different ways of individual and collective defence in face of suffering at work. As a conclusion, it was emphasised that knowing the experiences generating pleasure and suffering is fundamental in order to think the organization and processes of work and to improve workers‟ health and quality of work. Furthermore, it was indicated that knowing the ways of defence provides workers with a better knowledge of them selves and it also allows rethinking practices of care and relationships at work. The study follows the Resolution 466/12 of the National Health Council, with Certificate of Presentation for Ethical Appreciation under the number 40610415.7.0000.5346.